Design of dental implant using design of experiment and topology optimization: A finite element analysis study. (February 2021) - Gupta, Yash; Iyer, Rohit; Dommeti, Vamsi Krishna; Nutu, Emil; Rana, Masud; Merdji, Ali; Biswas, Jayanta Kumar; Roy, Sandipan
Ever since the introduction of topology optimization into the industrial and manufacturing fields, it has been a top priority to maximize the performance of any system by optimizing its geometrical parameters to save material while keeping its functionality unaltered. The purpose of this study is to design a dental implant macro-geometry by removing expendable material using topology optimization and to evaluate its biomechanical function. Three-dimensional finite element models were created of an implant embedded in cortical and cancellous bone. Parameters like the length and diameter of the implant and the bone quality (±20% variation in Young's modulus, Poisson's ratio and density for both cortical and cancellous bone) were varied to evaluate their effect on the principal stresses induced on the peri-implant bone tissues and the micromotion of the implant at 150 N applied load. Design optimization is used to select one suitable implant for each material property combination with optimum parameters that experiences the least von Mises stress and axial deformation, out of twenty implants with different length and diameter for each material property combination. Topology optimization was then used on the selected implants to remove the redundant material. The biomechanical functions of the implants with optimized parameter and volume were then evaluated. The finite element analyses estimated that a reduction of 32% to 45% in the implant volume is possible with the implant still retaining all of its functionality.